Cell-cell communication in diabetic retinopathy. (October 2017) - Roy, Sayon; Kim, Dongjoon; Lim, Remington
Abstract: In diabetic retinopathy, high glucose (HG)-mediated breakdown in cell-cell communication promotes disruption of retinal homeostasis. Several studies indicate that HG condition alters expression of connexin genes and subsequent gap junction intercellular communication (GJIC) in retinal vascular cells and non-vascular cells. A serious consequence of disrupted cell-cell communication is apoptosis and breakdown of the blood-retinal barrier (BRB). More recently, studies suggest adverse effects from HG on retinal Müller cells. This article focuses on HG-mediated changes in connexin expression and GJIC and their subsequent effects on the breakdown of retinal homeostasis, cell death, compromised vascular permeability, and interactions between endothelial cells, pericytes and retinal Müller cells in the pathogenesis of diabetic retinopathy. Additionally, options for rectifying disrupted homeostasis under HG condition associated with diabetic retinopathy are reviewed.